Hadis Sahih Al-Bukhari Yang Diklaim Munqathi’ Telaah Ulang Penilaian Muhibbin Tentang Riwayat Al-Hasan Al-Basri - M. Syukrillah (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2023)
The Sahih Al-Bukhari’s was claimed as the highest of validity (Sahih) after the Holy al-Quran. In the fact that its hadith was triggered criticism by academic researchers. Therefore, the study of this book was massively done. Muhibbin was one of them. In submission of thesis to Post Graduate Program of IAIN Sunan Kalijaga Yogyakarta in 2003 (Telaah Ulang Atas Kriteria Kesahihan Hadis-Hadis al-Jami’ al-Sahih”) the connectedness of some hadiths chain in Sahih al-Bukhari has been refused e.g., the isnad of al-Hasan ‘an Abi Bakrah. Through library research, this article attempts to evaluate, analyze, and criticize Muhibbin’s argumentation. The results of study were (1) the Isnad of al-Hasan from Abi Bakrah was not munqathi’. The isnad is fulfill recruitment of itthisal isnad. (2) the existence of some transmissions of al-Hasan from his teacher, Abi Bakrah via another narrator likes al-Ahnaf bin Qais should not contradicted with direct transmission of al-Hasan, (3) Isnad Assessment of al-Hasan from Abi Bakrah transmission wasn’t a subjectivity of al-Bukhari himself. (4) Muhibbin’s opinion had limited reference that only based on al-Daruquthy commentary and did not a wish to collect more information and examine the true of it. In the fact that al-Daruquthny himself narrated the transmission of al-Hasan ‘an Abi Bakrah in his Sunan.